Role of Knowledge Creation and Absorptive Capacity: A Panel Data Study of Innovation - Hameed, Kamran; Arshed, Noman; Munir, Mubbasher (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- Knowledge creation refers to the ability of firms to create new knowledge that starts from individuals to integrating the firms and then the overall economy. This study suggests that knowledge acquisition in a country has a significant relationship with innovative performance. Design/Methodology- Data from 48 highly HDI countries is taken from World Bank and World Economic Forum. Based on 480 country-year observations in a panel mediator model, it is revealed that the national efforts of boosting knowledge acquisition influence the firms’ innovative performance. Findings- Further, it is found that absorptive capacity in the employability of knowledgeable workers works as a mediator between knowledge acquisition and innovation. Whereby higher knowledge acquisition leads to higher absorptive capacity and higher innovation. Practical Implications- This study builds a quantitative model for the macroeconomic context of knowledge-based view.